1998
DOI: 10.1046/j.1365-2389.1998.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow rate on the adsorption and desorption of glyphosate, simazine and atrazine in columns of sandy soils

Abstract: Summary Adsorption and desorption of the herbicides glyphosate [N‐phosphonomethyl‐aminoaceticacid], simazine [6‐chloro‐N,N′‐diethyl‐1,3,5‐triazine‐2,4‐diamine] and atrazine [6‐chloro‐N2‐ethyl‐N4‐isopropyl‐1,3,5‐triazine‐2,4‐diamine] were studied in four sandy soils from Western Australia. Distribution coefficients (Kds) were calculated from breakthrough curves (BTCs) resulting from leaching step changes in concentrations through small saturated columns of soil at flow rates ranging from 0.3 to 30 m day–1. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 26 publications
3
22
0
2
Order By: Relevance
“…However, past the lapse of sufficient time the solid humic acid was hydrated and became plastic that is deformable and in some cases broke into smaller aggregates, exposing new adsorption sites. Similar 'steps' in experiments in soil packed beds have also been observed by Beltran et al (1998) and Bouchard (1999).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…However, past the lapse of sufficient time the solid humic acid was hydrated and became plastic that is deformable and in some cases broke into smaller aggregates, exposing new adsorption sites. Similar 'steps' in experiments in soil packed beds have also been observed by Beltran et al (1998) and Bouchard (1999).…”
Section: Resultssupporting
confidence: 78%
“…Relevant studies have concentrated on the effect of humic acid hydration on sorption (Graber and Borisover, 1998;Borisover and Graber, 2002) or on the use of various spectroscopic techniques (Martin-Neto et al, 1994;Davis and Jabeen, 2003). Batch and column techniques have been used for kinetic and non-equilibrium sorption studies (Sposito et al, 1996;Beltran et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Beltran et al (1998) found that adsorption of glyphosate in soil decreased with increasing flow rate. Increase of mobility was up to 50% for the highest flow rates.…”
Section: Introductionmentioning
confidence: 97%
“…Finally, glyphosate and phosphate have been reported to exhibit similar sorption mechanisms, thereby leading to potential competition for sorption sites (Gimsing and Borggaard 2002). These sorption mechanisms are evidenced by the influence of clay content (Beltran et al 1998;Borggaard and Gimsing 2008;da Cruz et al 2007;Dion et al 2001;Ololade et al 2014;Pessagno et al 2008;Singh et al 2014;Xu et al 2009), iron-and aluminum-oxide content (de Jonge et al 2001;Gimsing et al 2004Gimsing et al , 2007Mamy and Barriuso 2005;Morillo et al 2000;Pessagno et al 2008;Wang et al 2005), pH (Accinelli et al 2005;Al-Rajab et al 2008;Borggaard and Gimsing 2008;da Cruz et al 2007;de Jonge and Wollesen de Jonge 1999;Dousset et al 2007;Gimsing et al 2004;Mamy and Barriuso 2005;Xu et al 2009;Zhou et al 2004), phosphorus content (de Jonge et al 2001;Gimsing and Borggaard 2002), organic carbon (Albers et al 2009;da Cruz et al 2007;Morillo et al 2000;Ololade et al 2014;Pessagno et al 2008;Wang et al 2005) and the cation exchange capacity (CEC) (da Cruz et al 2007;de Jonge and Wollesen de Jonge 1999;Mamy and Barriuso 2005;…”
Section: Introductionmentioning
confidence: 99%